2022
DOI: 10.1093/ejcts/ezac211
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi Consensus report from the "Prolonged Air Leak: A Survey" study group on prevention and management of postoperative air leaks after minimally invasive anatomical resections

Abstract: OBJECTIVES This study reports the results of an international expert consensus process evaluating the assessment of intraoperative air leaks (IAL) and treatment of postoperative prolonged air leaks (PAL) utilizing a Delphi process, with the aim of helping standardization and improving practice. METHODS A panel of 45 questions was developed and submitted to an international working group of experts in minimally invasive lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Recent consensus guidelines advice to classify air leaks as mild (<100 ml/min), moderate (100–400 ml/min) and severe (>400 ml/min). 54 In other studies, intraoperative PAL >500 ml/min or >9.5% of the inspiratory tidal volume have been found to be predictive of pPAL. 55,56 Similar classification might also apply to larger animals such as sheep and pigs.…”
Section: Discussionmentioning
confidence: 83%
“…Recent consensus guidelines advice to classify air leaks as mild (<100 ml/min), moderate (100–400 ml/min) and severe (>400 ml/min). 54 In other studies, intraoperative PAL >500 ml/min or >9.5% of the inspiratory tidal volume have been found to be predictive of pPAL. 55,56 Similar classification might also apply to larger animals such as sheep and pigs.…”
Section: Discussionmentioning
confidence: 83%
“…Grading of Recommendations, Assessment, Development and Evaluation (GRADE) is a tool that systematic reviewers and guideline developers use to evaluate the quality of evidence and determine whether to propose an intervention (1). GRADE is distinct from previous appraisal tools.…”
Section: What Is Grade Methodology?mentioning
confidence: 99%
“…The lack of evidence-based guidelines on PAL burdens the routine activity of the thoracic surgeon, especially in the younger generation. Recently, the PALAS Study Group, through an international 3-round Delphi survey, reached an agreement on some relevant issues concerning the detection and management of intraoperative alveolar air leak and PAL but failed on others (1).…”
Section: Introductionmentioning
confidence: 99%
“…Operative closure remains a radical treatment for PAL. 9 Furthermore, it enables the use of patient-specific appropriate postoperative antibacterial therapy and pyothorax prophylaxis in patients with a high PAL risk score. We consider that both treatment strategies have the potential to be effective and that aggressive treatment strategies should not be ruled out in cases with a high-risk of PAL.…”
Section: F I G U R Ementioning
confidence: 99%
“…Some studies have shown that DDS measurements of postoperative air leak flow 8 and air leak patterns can predict PAL 2 . In practice, at many institutions, there is already an expert consensus that the air leak volume is a useful predictor of subsequent PAL 9 . Few prediction models have focused on the intrapleural pressure and its fluctuations 10,11 .…”
Section: Introductionmentioning
confidence: 99%